2-D zinc ferrite "moss" furred on 3-D zinc oxide tetrapods to boost detection sensitivity of hydrogen sulfide. (January 2021) - Li, Dong; Ma, Ji; Chen, Kezheng
Abstract: In this study, a two-/three-dimension (2D/3D) architecture was designed and fabricated by a facile dip-calcination procedure. In this design, moss-like zinc ferrite (ZnFe2 O4 ) was grown on the surface of 3D zinc oxide tetrapods (ZnO-T) to form a semiconductor heterostructure. This unique architecture features the merits of copious porosities that facilitate gas circulation and boost active gas-absorption sites, making it exceedingly applicable for gas detection. It was found that this architecture was very sensitive towards hydrogen sulfide gas (H2 S, 2 ppm, 250 °C, 65% RH) with ultrafast response and recovery time of 2 and 9 s, respectively. Further, low-concentration gas tests at 250 °C, 65% RH unraveled that it showed quick response even when the concentration of H2 S gas was as low as 0.6 ppb. Highlights: A two-/three-dimension architecture was designed for gas detection. It was found that this architecture had an ultra-fast response speed to H2 S gas. The detection limit of the architecture for H2 S gas is as low as 0.6 ppb at 250 °C.